2006
DOI: 10.1097/00005082-200605000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Physical Impairment, and Treatment of Depression in Chronic Heart Failure

Abstract: Attitudes about impairment and perceived social support were the strongest cross-sectional correlates of depression. The strong association between physical impairment and depression was no longer significant after controlling for attitudes about impairment. In addition, attitudes about impairment predicted chronicity of depressive symptoms longitudinally after controlling for baseline depressive symptom severity. The relation between physical impairment and depression in heart failure is strongly related to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
0
27
1
Order By: Relevance
“…Among Japanese elderly with arthritis, Nakajima et al (2006) has found that self-rated poor general health and greater functional disability was associated with depression. In patients with heart failure, attitudes towards functional impairment and perceived social support were found to be strong contributing factors for depression (Turvey et al, 2006). Nevertheless, in the present study, for a number of illnesses (chronic respiratory disease, gastric problems, arthritis, and heart failure), subjective poor health and functional disability did not completely explain the presence of depression.…”
Section: Discussioncontrasting
confidence: 88%
“…Among Japanese elderly with arthritis, Nakajima et al (2006) has found that self-rated poor general health and greater functional disability was associated with depression. In patients with heart failure, attitudes towards functional impairment and perceived social support were found to be strong contributing factors for depression (Turvey et al, 2006). Nevertheless, in the present study, for a number of illnesses (chronic respiratory disease, gastric problems, arthritis, and heart failure), subjective poor health and functional disability did not completely explain the presence of depression.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding complements previous research showing that difficulty adjusting to the limitations of illness is a major predictor of depression in patients with HF. 26 Participants, particularly family caregivers, stressed the need for additional support and mental health assistance to help with adjustment. A UK HF palliative care program found mental health assistance to be one of the most important elements of its services.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that conditions that cause signifi cant functional limitations are associated with cognitive dysfunction in patients with CHF (Turvey et al, 2006). In a cancer population Glaus (1998) identifi ed problems in thinking and lack of concentration as cognitive manifestations of tiredness.…”
Section: Fatigue In Patients With Chronic Heart Failurementioning
confidence: 99%